Recommendations for ultrasonographic assessment of renal arteries - Drelich-Zbroja, Anna (J Ultrason, 2018)
The present clinical practice recommendations are addressed to physicians of all specialties, who perform Doppler ultrasound examinations of the kidneys on a daily basis, and in particular to specialists in radiology and imaging diagnostics. The recommendations were based on the Ultrasonography Standards of the Polish Ultrasound Society and current scientific reports consistent with Evidence Based Medicine. The paper discusses patient preparation protocol, examinat ion technique with particular emphasis on patient’s position allowing to obtain proper Doppler angle of insonation, as well as diagnostic limitations of the technique. Normal blood flow parameters as well as those indicating hemodynamically significant stenosis are also presented. Although the 2013–2014 American guidelines for renal artery duplex sonography (AIUM Practice Parameter for the Performance of Native Renal Artery Duplex Sonography and AIUM Practice Guideline for the Performance of an Ultrasound Examination of Solid-Organ Transplants), which were the basis for many national recommendations, have not been significantly updated to date, a large body of scientific research indicates the need for revision of current Doppler ultrasound standards and parameters, particularly for patients receiving endovascular treatment due to renovascular hypertension. Therefore, the paper refers to the current issue of ultrasound scan interpretation in patients receiving endovascular stenting, after transplantation of kidney, as well as in pediatric patients.